Global trends in surface eddy mixing from satellite altimetry - Zhang, Guangchuang; Chen, Ru; Li, Laifang; Wei, Hao; Sun, Shantong (Frontiers in Marine Science, 2023)
Mixing induced by oceanic mesoscale eddies can affect tracer distributions in the ocean and thus modulate the evolution of the physical and biochemical marine system. In the context of global warming, regionally different trends in eddy mixing could exist. Motivated by this hypothesis, we quantified the trend in surface eddy diffusivity, a metric widely used to quantify the eddy mixing rate, in the global ocean using satellite altimetry data. The global average of the particle-based eddy diffusivity increases by 284.1 $\mathrm{m^2s^{-1}}$ per decade during the period of 1994-2017, or 3.7% per decade relative to its climatological mean value. In 54% of the global ocean, eddy diffusivity shows an increasing trend. The diffusivity trend can be decomposed into two components: one related to changes in eddy mixing length and the other related to eddy velocity magnitude. In 73% of the global ocean, changes in eddy mixing length account for more than 50% of the diffusivity trend. The suppressed mixing length theory (SMLT) is employed to interpret the trend in eddy mixing length. SMLT well captures the sign of the trend in two of the representative regions. Among all the parameters (e.g., eddy size, phase speed) inherent in SMLT, the eddy velocity magnitude plays a dominant role in determining the trend in the SMLT-based eddy mixing length. Diagnosing the geostrophic eddy kinetic energy budget reveals that the dominant mechanism for the trend in eddy velocity magnitude is the pressure work induced by ageostrophic flows. Our results suggest that a time-dependent eddy parameterization scheme should be employed in non-eddy-resolving models to account for the trend in eddy mixing.